Determinan Proporsi Dana Tabarru’ pada Lembaga Keuangan Asuransi Jiwa Syariah - Atika Suryani Harahap; Kamilah K. (ManBiz: Journal of Management and Business, 2023)
Financial management in Islamic insurance companies uses a split fund system. It is also supported by PMK Number 18/PMK.010/2020, which emphasizes that operators or sharia insurance companies must separate wealth by tabarru' fund obligations from the obligations and assets of company funds. The separation of funds has been carried out since participants pay contributions (premiums) at the beginning of the transaction. The purpose of this study is to analyze the factors that influence the proportion of tabarru' funds in Sharia Life Insurance companies. This research is a quantitative research, and the source of the data obtained is secondary data. The population is 21 Sharia Life Insurance companies registered with OJK. The sample of this study uses a purposive sampling technique by producing 16 sharia life insurance companies registered with the OJK, using annual financial statements according to the variables used during the period (2017-2019). Data analysis uses panel data regression analysis with fixed effects model which is processed using eviews 9. The findings from this research show that claims, sharia reinsurance, and operating expenses have a significant effect, while the growth of tabarru' funds and investment returns of tabarru' funds have no significant effect. With the coefficient of determination (R square) 0.775396 which means claims, sharia reinsurance, operating expenses, growth of tabarru' funds and investment returns of tabarru' funds can explain 77% of the proportion of tabarru' funds and the rest is influenced by other variables outside the study.. Keywords: Proportion of Tabarru' Funds, Sharia Life Insurance, Separation of Funds